Baraba Waldsteppe, Russland. Vom Jagen und Fischen zur Viehzucht in der Waldsteppe des Ob’-Irtysch Zwischenstromlands (Westsibirien). Bioarchäologische Forschungen in der Baraba Waldsteppe, Russland aus den Jahren 2018 bis 2020 - Reinhold, Sabine; Marchenko , Zhanna V. (e-Forschungsberichte des DAI, 2020)
One of the most important adaptations of societies at the northern frontier of the Eurasian steppe belt was the transition from a hunter-gatherer to a pastoral economy during the Bronze Age. The different hypothesis regarding this cultural and economic adaptation processes are studied by an ongoing German-Russian research project with a bioarchaeological research agenda focusing on the analysis of stable isotopes to reconstruct changes in diets and mobility pattern.